The perfect family - Boland, Shalini (London : Bookouture, 2018)
Gemma Ballantine is getting ready for work one morning when her eldest child comes running down the stairs, saying the words every mother dreads. The front door is open and her six-year-old daughter has disappeared. Frantic with fear, Gemma starts a nail-biting search for her little girl. After what feels like forever, her mother-in-law Diane finds Katie wandering lost a few streets away. Relieved to have her youngest child back in her arms, breathing in the sweet scent of her hair, Gemma thinks the nightmare is over. But then her perfect family starts to fall apart. And she realizes it's only just beginning.
Keywords: Families -- Fiction; Mother and child -- Fiction; Mothers -- Fiction; Thrillers (Fiction)